PENGARUH JUMLAH PASIEN RUANG RAWAT INAP KELAS I DAN II TERHADAP JUMLAH KOLONI BAKTERI PADA STETOSKOP DI SALAH SATU RUMAH SAKIT KOTA MALANG - Irme Adhitya (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2018)
Introduction: Nosocomial infection is one of the biggest killers in the world that occurs due to transmission of pathogens through medical devices such as stethoscopes. This is because the stethoscope has direct contact with the patient's skin. Another factor that affects is the density of patients in the treatment room. Therefore, this study wanted to know the effect of the number of patients in class I and II inpatient rooms on the number of bacterial colonies on the stethoscope.Methods: In vitro research by swab on the bell and membrane stethoscope used for patients in class I and II inpatient rooms. Swabs used sterile cotton swabs that had been dipped in 0.9% NaCl. Samples were inoculated into three types of media in order to determine the number and nature of bacterial colonies. The samples were incubated for 48 hours and then counted the number of bacterial colonies. Then a statistical test was done by Mann-Whitney U Test and Spearman correlation.Results: The bacterial colonies that grow are thought to be family of Enterobacteriaceae, Staphylococcus spp., E.coli or Klebsiella spp., and Salmonella spp, or Shigella spp. There were no significant differences in results (p> 0.05) between the number of bacterial colonies on the bell and the membrane stethoscope in class I and II inpatient rooms. There was no correlation (p> 0.05) between the number of patients and the number of bacterial colonies on the bell and membrane stethoscopeConclusion : The number of patients in class I and II inpatient rooms did not affect the number of bacterial colonies on the stethoscope.